PENERAPAN PEMULIHAN TRANSFORMATIF DIGITALISASI UMKM DI KOTA PADANG - Wise Maliha, Dabitha (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This article aims to elaborate on transformative recovery efforts digitization of SME’s in Padang city. The Covid-19 pandemic gives drastically impact on SME’s income. However, along gradually economic recovery, Padang City Government have been striving for transformative recovery through several programs to support SME’s digitalization ecosystem. This article uses a literature study method by analyze information from various literatures. The results show Padang City Government has implemented several programs in form of mentoring, training and socialization for SME’s actors that related on strategic steps prepared by The Ministry of Cooperatives and SME’s for realization of digital entrepreneurship ecosystem.Keywords: SME’s, Digital Entrepreneurship, Covid-19